Misguided and Modest: Reflections of Our Youth Voice Research - Stride, Annette; Brazier, Ruth; Fitzgerald, Hayley (Frontiers in Sports and Active Living, 2022)
In recent years, Physical Education (PE) has seen a growth in the commitment to youth voice research. This approach foregrounds the practice of researching with young people, rather than conducting research on or about them. Whilst we are cognisant of the many possibilities youth voice research offers, we are also concerned that there is a tendency to overlook the challenges of supporting youth voice activities. This paper draws on our collective reflections to bring to the fore some of the complexities we have encountered when attempting to engage in school-based youth voice research. We explore the following questions: How can youth voice research engage with different young people to capture a diversity of voices? What are the challenges of undertaking youth voice research? What are the possibilities of change through youth voice research? We consider these questions by drawing upon four principles of student voice work including communication as dialogue, participation and democratic inclusivity, unequal power relations, and change and transformation. We use these principles to critique our own research and, in doing so, draw on entries from our research diaries. The paper questions whether young people need help to share their insights and experiences about PE, or whether it is us - researchers, teachers and schools - who need help to more readily recognize and be attentive to young people's voices. We also point to the importance of recognizing modest change through youth voice research and the need to secure adult allies to support activities and potential outcomes. Engaging in youth voice research is an immersive and messy encounter that involves navigating a journey that is anything but straightforward. Even though this is the case, our moral and ethical compass continues to point us in this direction and we remain firm advocates of youth voice work. This paper offers a starting point for others to begin to grapple with the pitfalls and possibilities when supporting youth voice research.